Injectable cinnamaldehyde–loaded ZIF-8/Gallic Acid–Grafted gelatin hydrogel for enhanced angiogenesis and skin regeneration in diabetic wound healing - Zhou, Bo; Zhang, Chen; Dai, Sheng; Zhao, Jin; Li, Huaiyu; Peng, Yanbin; Chu, Yunfeng; Chen, Zhong; Qin, Haotian; Zeng, Hui (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundChronic diabetic wounds remain a major clinical challenge due to persistent ischemia, oxidative stress, and impaired angiogenesis. Injectable hydrogels capable of adapting to irregular wound beds and delivering bioactive cues offer promising therapeutic potential for enhancing tissue regeneration.MethodsWe developed a multifunctional injectable hydrogel by incorporating cinnamaldehyde-loaded ZIF-8 nanoparticles (CA@ZIF-8) into a gallic acid–grafted gelatin (GGA) matrix, followed by transglutaminase-mediated crosslinking. The physicochemical characteristics, drug release behavior, and mechanical performance of the CA@ZIF-8/GGA hydrogel were systematically evaluated. In vitro assays using human umbilical vein endothelial cells (HUVECs) were conducted to assess cytocompatibility and angiogenic activity. A full-thickness skin wound model in streptozotocin-induced diabetic rats was employed to evaluate in vivo wound healing efficacy and biocompatibility.ResultsThe CA@ZIF-8/GGA hydrogel exhibited favorable injectability, enhanced mechanical strength, and sustained release of both cinnamaldehyde and Zn2+. In vitro, the hydrogel significantly promoted HUVEC proliferation, migration, and tube formation, accompanied by upregulated expression of CD31 and VEGF. In vivo, CA(0.6)@ZIF-8/GGA-treated wounds demonstrated accelerated closure, enhanced granulation tissue formation, increased neovascularization, and re-epithelialization compared with control groups. No histological abnormalities were observed in major organs, indicating good systemic biocompatibility.ConclusionThis study presents an injectable CA@ZIF-8/GGA composite hydrogel that effectively promotes angiogenesis and diabetic wound regeneration. The synergistic integration of MOF-based controlled release and polyphenol-enhanced bioactivity highlights its potential as a clinically translatable platform for chronic wound management.